The ‘Toolbox’ of strategies for managing Haemonchus contortus in goats: What’s in and what’s out - Kearney, P.E.; Murray, P.J.; Hoy, J.M.; Hohenhaus, M.; Kotze, A. (Veterinary parasitology, 2016)
•The large variety of strategies that have been investigated in the past several decades for managing/treating Haemonchus contortus were reviewed.•Of these, the major strategies were selected for discussion in this review.•Evaluation of these strategies as to their current availability, feasibility, economical cost and potential ease of implementation depending on the systems of production and their complementary nature when used together.•A final model of strategies available to goat production systems for managing Haemonchus contortus. A dynamic and innovative approach to managing the blood-consuming nematode Haemonchus contortus in goats is critical to crack dependence on veterinary anthelmintics. H. contortus management strategies have been the subject of intense research for decades, and must be selected to create a tailored, individualized program for goat farms. Through the selection and combination of strategies from the Toolbox, an effective management program for H. contortus can be designed according to the unique conditions of each particular farm. This Toolbox investigates strategies including vaccines, bioactive forages, pasture/grazing management, behavioural management, natural immunity, FAMACHA, Refugia and strategic drenching, mineral/vitamin supplementation, copper Oxide Wire Particles (COWPs), breeding and selection/selecting resistant and resilient individuals, biological control and anthelmintic drugs. Barbervax®, the ground-breaking Haemonchus vaccine developed and currently commercially available on a pilot scale for sheep, is prime for trialling in goats and would be an invaluable inclusion to this Toolbox. The specialised behaviours of goats, specifically their preferences to browse a variety of plants and accompanying physiological adaptations to the consumption of secondary compounds contained in browse, have long been unappreciated and thus overlooked as a valuable, sustainable strategy for Haemonchus management. These strategies are discussed in this review as to their value for inclusion into the ‘Toolbox’ currently, and the future implications of ongoing research for goat producers. Combining and manipulating strategies such as browsing behaviour, pasture management, bioactive forages and identifying and treating individual animals for haemonchosis, in addition to continuous evaluation of strategy effectiveness, is conducted using a model farm scenario. Selecting strategies from the Toolbox, with regard to their current availability, feasibility, economical cost and potential ease of implementation depending on the systems of production and their complementary nature, is the future of managing H. contortus in farmed goats internationally and maintaining the remaining efficacy of veterinary anthelmintics.